2023
DOI: 10.1063/5.0159112
|View full text |Cite
|
Sign up to set email alerts
|

Droplet evaporation on superhydrophobic surfaces

H. Y. Erbil,
G. McHale

Abstract: Over the last decades, a fabulous variety of synthetic superhydrophobic surfaces have been created, offering unique anti-wetting properties. A significant focus for these surfaces has been on their stay-dry and self-cleaning properties. However, unless in a saturated environment, water droplets lose mass through evaporation and this itself is a field of significant interest, which is illustrated by a flood of recent studies on surface contamination and potential surface transmission of infection by evaporating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 128 publications
(303 reference statements)
0
3
0
Order By: Relevance
“…ref. 42 and 80), specifically in the way the fractal scaling is treated and in the consistency relationship between the fractal dimension and the effective surface area of the polymeric samples.…”
Section: Resultsmentioning
confidence: 99%
“…ref. 42 and 80), specifically in the way the fractal scaling is treated and in the consistency relationship between the fractal dimension and the effective surface area of the polymeric samples.…”
Section: Resultsmentioning
confidence: 99%
“…204 The evaporation of sessile droplets on such surfaces has also been characterized recently. 205,206 More detailed reviews of distinct aspects of sessile droplet evaporation can be found elsewhere, such as evaporation on superhydrophobic substrates, 207 and an analytical description of the process. 208 In addition to well-studied contact line dynamics, the solid− liquid interaction during evaporation affects thermal and internal flow fields.…”
Section: ■ Interaction Of Liquid With Surfacesmentioning
confidence: 99%
“…Similarly, evaporation of sessile droplets is also analyzed on soft viscoelastic surfaces, , where, for instance, a deformation near the contact line can impact the wetting transition affecting the overall evaporation process. , Interestingly, in an effort to battle the COVID-19 pandemic, the viability of virus-laden droplets on different surfaces is also studied using droplet evaporation as the primary fundamental mechanism. , With the ongoing research efforts to create surfaces with unique wetting properties, biphilic substrates also have gained attention . The evaporation of sessile droplets on such surfaces has also been characterized recently. , More detailed reviews of distinct aspects of sessile droplet evaporation can be found elsewhere, such as evaporation on superhydrophobic substrates, and an analytical description of the process …”
Section: Interaction Of Liquid With Surfacesmentioning
confidence: 99%
“…The combination of these features makes evaporating sessile droplets with dispersed particles an intriguing and challenging topic for research. Recently, intense research has been conducted on this topic as suggested by the number and the quality of reviews and books published in the past decade. …”
Section: Introductionmentioning
confidence: 99%